The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1016/s1084-8592(00)00008-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating epithelial cells after surgery for benign bereast disease

Abstract: This finding shows that benign epithelial cells can be mobilized during breast surgery; this effect of surgical manipulation warrants caution in the interpretation of RT-PCR positivity for cytokeratin mRNA in the peripheral blood of patients undergoing surgery for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The MCF-7 cell line, used as a model for CTC selection and enumeration via the integrated HTMSU, is a breast cancer cell line that possesses an overexpressed membrane antigen termed the epithelial cell adhesion molecule, EpCAM. MCF-7 cells are typically 15−30 μm in diameter (mean = 24 μm) and have been closely associated with micrometastatic breast cancer . EpCAM occurs at a frequency of 5.1 × 10 5 molecules per cell .…”
Section: Resultsmentioning
confidence: 99%
“…The MCF-7 cell line, used as a model for CTC selection and enumeration via the integrated HTMSU, is a breast cancer cell line that possesses an overexpressed membrane antigen termed the epithelial cell adhesion molecule, EpCAM. MCF-7 cells are typically 15−30 μm in diameter (mean = 24 μm) and have been closely associated with micrometastatic breast cancer . EpCAM occurs at a frequency of 5.1 × 10 5 molecules per cell .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, for positive enrichment methods, one type of antigen, the epithelial surface tumor marker (EpCAM), is targeted and typically results in a high-purity separation depending on the antigen. With this method, only CTCs originating in epithelial tumor (breast, colon, prostate, and lung) scans are captured [82], but in recent studies, nonmalignant epithelial cells with the same antigen characteristics have been found in patients with benign colon [82], pancreatic [83], and breast [84, 85] diseases. Nonmalignant tumor cells that have similar characteristics as epithelial CTCs may result in false-positive results; thus, it is also important to consider epithelial-to-mesenchymal transition (EMT) and stem cell markers.…”
Section: Technologies For Ctc Enrichment From Whole Blood Samplesmentioning
confidence: 99%
“…For example, previous researches have used commercial antibodies specific to epithelial antigens for isolation of CTCs, thus enriching the benign epithelial cells and CTCs in the blood indiscriminately and giving false-positive results591011. Several papers have found epithelial cells in the blood of subjects without malignancy, such as the patients with benign inflammatory colon disease11, benign bowel disease28, or epithelial proliferative disease2930, and the subjects after the surgery of benign breast cancer31. These epithelial normal cells were detectable with current CTC assays, indicating the need for further characterization of the cells.…”
Section: Resultsmentioning
confidence: 99%